Giant Cervico-Mediastinal Myxolipoma in a 6 Year Old Child - Manish Gupta; Naiya Rao; Maitrayee Roy (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2017)
Lipomas are benign mesenchymal tumors that may present anywhere on the body. However, myxolipoma, the histological variant is rarely seen. We report a rare case of giant anterior cervicomediastinal myxolipoma in a 6 year old child, with discussion over diagnostic and management strategies for same.